Gene expression response to a nematode parasite in novel and native eel hosts - Bracamonte, Seraina Emilia; Johnston, Paul R.; Monaghan, Michael T.; Knopf, Klaus (Humboldt-Universität zu Berlin, 2019)
Invasive parasites are involved in population declines of new host species worldwide. The high susceptibilities observed in many novel hosts have been attributed to the lack of protective immunity to the parasites which native hosts acquired during their shared evolution. We experimentally infected Japanese eels (Anguilla japonica) and European eels (Anguilla anguilla) with Anguillicola crassus, a nematode parasite that is native to the Japanese eel and invasive in the European eel. We inferred gene expression changes in head kidney tissue from both species, using RNA-seq data to determine the responses at two time points during the early stages of infection (3 and 23 days postinfection). At both time points, the novel host modified the expression of a larger and functionally more diverse set of genes than the native host. Strikingly, the native host regulated immune gene expression only at the earlier time point and to a small extent while the novel host regulated these genes at both time points. A low number of differentially expressed immune genes, especially in the native host, suggest that a systemic immune response was of minor importance during the early stages of infection. Transcript abundance of genes involved in cell respiration was reduced in the novel host which may affect its ability to cope with harsh conditions and energetically demanding activities. The observed gene expression changes in response to a novel parasite that we observed in a fish follow a general pattern observed in amphibians and mammals, and suggest that the disruption of physiological processes, rather than the absence of an immediate immune response, is responsible for the higher susceptibility of the novel host. Peer Reviewed